(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe clinical and laboratory characteristics of upper gastrointestinal bleeding patients and evaluate the Blatchford score’s prognostic value in predicting medical intervention requirements. Methods: A retrospective cross-sectional study of 53 patients with upper gastrointestinal bleeding due to peptic ulcer disease admitted to the Emergency Department of Duc Giang General Hospital from March to August 2025. Results: Mean age was 66.8 years with 83% male predominance. Blatchford score ≥ 6 was present in 90.6% of patients. Medical intervention was required in 73.6% of cases. At cutoff ≥ 6, the score showed excellent sensitivity (100%), negative predictive value (100%), and accuracy (92.5%). Blatchford ≥ 6 points (OR = 15.8, p = 0.003) and high-risk Forrest classification IA-IIB (OR = 8.5, p = 0.007) were independent predictors of medical intervention. Conclusion: The Blatchford score is a valuable tool for early risk stratification in emergency settings, accurately identifying low-risk patients who may not require urgent intervention.